2020
DOI: 10.1074/jbc.rev120.010856
|View full text |Cite
|
Sign up to set email alerts
|

Iron homeostasis and plant immune responses: Recent insights and translational implications

Abstract: Iron (Fe) metabolism and the plant immune system are both critical for plant vigor in natural ecosystems and for reliable agricultural productivity. Mechanistic studies of plant iron homeostasis and plant immunity have traditionally been carried out in isolation from each other; however, our growing understanding of both processes has uncovered significant connections. For example, iron plays a critical role in the generation of reactive oxygen intermediates during immunity and has been recently implicated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 164 publications
(186 reference statements)
1
71
0
1
Order By: Relevance
“…Collectively, this comparative analysis across small sets of MAGs with differential abundance across drought stress reveals both new and previously identified links between functional categories and drought enrichment status. Interestingly, several recent studies have revealed connections between plant microbiome regulation and inorganic ion transport and metabolism, including those that have identified relationships between phosphate and iron homeostasis and microbiome regulation 29,30 . Additionally, other work has suggested that plant nutrient status may be directly perturbed by drought stress 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, this comparative analysis across small sets of MAGs with differential abundance across drought stress reveals both new and previously identified links between functional categories and drought enrichment status. Interestingly, several recent studies have revealed connections between plant microbiome regulation and inorganic ion transport and metabolism, including those that have identified relationships between phosphate and iron homeostasis and microbiome regulation 29,30 . Additionally, other work has suggested that plant nutrient status may be directly perturbed by drought stress 31 .…”
Section: Resultsmentioning
confidence: 99%
“…FPN is also a major player in the iron-immunity crosstalk; interference with iron acquisition by pathogens is a critical component of the immune response and is a widespread mechanism, present also in plants [ 8 ]. Several studies have shown the importance of macrophage FPN in infections, with distinct effects on pathogen growth according to whether microbes are extracellular or intracellular [ 19 , 77 , 78 ].…”
Section: Role Of Ferroportin-mediated Modulation Of Local Iron Avamentioning
confidence: 99%
“…The control of iron balance is particularly crucial in the context of infection/inflammation, in which pathogens use multiple mechanisms to acquire iron, whereas the host sequesters iron and starves them of this essential metal. The universality of this response is highlighted by the appreciation that this competition for iron occurs also in plants, as iron sequestration is important for plant immune responses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…How can soil-and benzoxazinoid-dependent leaf iron homeostasis explain fall armyworm performance? In theory, iron homeostasis may indirectly affect leaf quality by changing leaf primary metabolism and defense expression (36)(37)(38), or directly by acting as a herbivore micronutrient (22). To test the first hypothesis, we measured soluble protein, hydrolysable amino acid and carbohydrate levels in the leaves of WT and bx1 mutant plants grown under different iron regimes (Fig.…”
Section: Changes In Leaf Herbivore Performance Are Not Explained By Changes In Leaf Primary Metabolism and Defense Expressionmentioning
confidence: 99%